Strategi Pendidikan Keagamaan Berbasis Digital: Studi Model Komunikasi Edukatif Pesantren Nurul Jadid Melalui Facebook - Muhammad Iqbal; Mahfudz (Yayasan Literasi Altruis Khatulistiwa, 2025)
Digital transformation has prompted Islamic educational institutions, such as Islamic boarding schools, to develop new communication strategies to convey religious values while fulfilling their educational functions. One notable strategy is the use of social media as a medium for non-formal religious education. This study aims to analyse the digital-based religious education strategies developed by Pondok Pesantren Nurul Jadid through its official Facebook account during March–June 2025. The study employs a qualitative approach using content analysis on all posts published during the period. Data were analysed using four main categories: message type, language style, religious symbols, and audience interaction. The results of the study indicate that the Facebook messages of the Nurul Jadid Islamic Boarding School are not merely informative or ceremonial but are deliberately crafted to foster religious awareness, strengthen Islamic literacy, and expand the educational functions of the boarding school in the digital realm. The language style used is communicative and polite, interspersed with popular elements that facilitate public acceptance in the digital sphere. Religious symbols such as the yellow book, mosque, and religious leaders serve as visual representations of Islamic educational values. The highest audience interaction occurs on video content and religious moments, indicating the effectiveness of content as an educational medium. This study concludes that Facebook is part of the pesantren's educational communication strategy in integrating traditional and modern values, and in shaping a digital media-based religious education model relevant to the current public character